Analisis Pola Kecacatan dan Kinerja Proses Perakitan Produk Kursi Kuliah Menggunakan Metode Statistical Process Control - Aqidawati, Era Febriana; Nugraha, Isna; Khofiyah, Nida An; Istiqomah, Silvi; Putra, Perdana Suteja (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The furniture manufacturing industry is required to consistently produce products that meet dimensional and functional specifications to minimize rework, scrap, and resource waste. This study applies Statistical Process Control (SPC) to assess the quality performance of lecture chair production in a furniture company. Pareto analysis identified the seat and table board as the main sources of defects. The -R control chart and p and np charts indicate a stable process, and the Cp value (1.01–2.07) indicates that the process is capable. However, the average defect proportion of 0.46 per lot indicates that the defect rate is still operationally high. The data suggests that most quality problems are caused by general process variations related to people, methods, and machines. Therefore, improvements should focus on making work more consistent and better controlling processes.